A better way to manage the neck of clinically N0 oral squamous cell carcinoma patients?. Issue 1 (January 2022) - Yick, Michelle Che Ting; McGurk, Mark; Schilling, Clare
Abstract : Introduction: Currently, elective neck dissection (END) is the commonest neck management of clinically staged T1–2 N0 M0 (cT1–2 cN0 cM0) oral squamous cell carcinoma (OSCC) patients. However, 70–80% of these patients do not carry occult cervical lymph node metastases, and hence are overtreated by END. Sentinel node biopsy (SNB) is an intraoperative staging method that aims to identify occult cervical lymph node metastases, hence preventing unnecessary neck dissection. This study investigated whether SNB is an appropriate alternative to END for this patient population. Methods: A multicentre retrospective analysis of 51 SNB-treated and 62 END-treated cT1–2 cN0 cM0 OSCC patients at two hospitals in England in 2017–2018 was performed. Survival outcomes and treatment-associated complications were compared between the two groups. Results: END patients had a greater median age (END=68 years versus SNB=63 years) and proportion of T2 tumours (END=57.9% versus SNB=25.5%). There was no significant difference in occult metastases rate between the two groups (SNB=23.5% versus END=25.8%). SNB-treated patients had no significant difference in 3-year relapse-free survival (SNB=90.2% versus END=87.1%), 3-year overall survival (SNB=72.5% versus END=72.6%) and 3-year disease-specific survival (SNB=86.3% versus END=90.3%) versus END-treated patients. However, SNB-treated patients had significantly fewer incidences of post-operative lymphoedema (p=0.000012), nerve damage (p=0.00787), neck stiffness (p<0.00001) and limited shoulder mobility (p=0.00390). Conclusions: This study reflects real-world outcomes after NICE recommended SNB in 2016. SNB is a less invasive neck management which does not significantly reduce survival outcomes, but significantly reduces treatment-associated complications versus END, and hence may be an attractive alternative to END.